The clinical efficacy of collagen dressing on chronic wounds: A meta-analysis of 11 randomized controlled trials - Shu, Hongxin; Xia, Zhiyu; Qin, Xuan; Wang, Xiaowei; Lu, Weihang; Luo, Qingyu; Zhang, Zhenxiong; Xiong, Xiaowei (Frontiers in Surgery, 2022)
ABSTRACT Objective: To evaluate the clinical efficacy of collagen dressing for patients with chronic wounds. Materials and methods: Relevant randomized controlled trials were searched from the databases such as PubMed, EMBASE, and the Cochrane library as of January of 2022. For dichotomous outcomes and continuous outcomes, risk ratio and mean difference was calculated, respectively. Subgroup analysis was performed according to the type of chronic ulcer and follow-up. Additionally, trial sequential analysis (TSA) was performed to further verify the results. Jadad score was used to assess the quality of trials. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) was utilized to assess the level of evidence for outcomes. Results: In total, 11 studies, a total of 961 patients of whom 485 in collagen group were included. Compared with standard of care (SOC) alone, the group of adding an extra collagen dressing achieved higher wound healing rate (Risk Ratio, 1.53; 95% CI, 1.33 to 1.77). The collagen group also showed a greater healing velocity than SOC group (Mean Difference, 2.69; 95% CI, 0.87 to 4.51). In addition, the adverse events related to dressing between two groups were similar (Risk Ratio, 0.67; 95% CI, 0.44 to 1.01). Conclusions: Collagen dressing increases wound healing rate and may be an effective and safe treatment for chronic wounds management. However, more extensive research shall be conducted to substantiate these results.